Kontribusi Motivasi Kerja dan Kompetensi Individu terhadap Kinerja dan Penjualan Salesperson - Cecep Hidayat; Sisca Cintra (Bina Nusantara University, 2010)
This study has two objectives; first, knowing the job motivation and individual competence contribution towards the performance of salesperson at Ray White Cengkareng. Second, knowing the job motivation, individual competence, performance contribution towards selling of salesperson at Ray White Cengkareng. The type of this study used is associative survey and the analysis technique used is the path analysis. The data are obtained through a survey with questionnaire as the main instrument which were distributed to salesperson and manager of Ray White Cengkareng who were chosen as respondents. The results of this study indicate that the job motivation and individual competence contributes simultaneously and significantly towards the performance of salesperson. Besides, the job motivation, individual competence, and performance contribute simultaneously and significantly towards selling of salesperson.